2021
DOI: 10.1101/2021.03.20.21253838
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The General Psychopathology Factor from Early to Middle Childhood: Longitudinal Genetic and Risk Analyses

Abstract: Background: Accumulating research suggests the structure of psychopathology is best represented by continuous higher-order dimensions, including a general dimension, p-factor, and more specific dimensions, such as externalizing and internalizing factors. Here, we aimed to 1) replicate the p-factor in early childhood; 2) externally validate the dimensions with measures relating to mental health; 3) examine stability and change of the genetic and environmental influences on the dimensions of psychopathology fro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Twin and family studies have highlighted how a single genetic dimension partly underlies diverse disorders (Lichtenstein et al, 2009;Pettersson, Anckars äter, Gillberg, & Lichtenstein, 2013;Pettersson, Larsson, & Lichtenstein, 2016). Similar investigations across childhood have pointed to substantial genetic contributions to the general psychopathology factor (P), as well as substantial genetic stability of P across time (Allegrini et al, 2020;Avinun, Knafo-Noam, & Israel, 2021). Such investigations rely on modelling common and specific psychopathology dimensions with hierarchical models, such as second-order and bifactor models (Figure 2G-H).…”
Section: Phenotypic Stability and Specificitymentioning
confidence: 96%
“…Twin and family studies have highlighted how a single genetic dimension partly underlies diverse disorders (Lichtenstein et al, 2009;Pettersson, Anckars äter, Gillberg, & Lichtenstein, 2013;Pettersson, Larsson, & Lichtenstein, 2016). Similar investigations across childhood have pointed to substantial genetic contributions to the general psychopathology factor (P), as well as substantial genetic stability of P across time (Allegrini et al, 2020;Avinun, Knafo-Noam, & Israel, 2021). Such investigations rely on modelling common and specific psychopathology dimensions with hierarchical models, such as second-order and bifactor models (Figure 2G-H).…”
Section: Phenotypic Stability and Specificitymentioning
confidence: 96%
“…The higher-order factor that accounts for the strong covariation of specific psychopathologies (e.g., externalizing psychopathology, internalizing psychopathology) is referred to as general psychopathology or p factor when including a thought disorder dimension (e.g., obsessions and compulsions, and mania; Caspi et al, 2014). Some have suggested that including a general psychopathology or p factor is necessary to fully conceptualize the structure of psychopathology (Avinun et al, 2021;Lahey et al, 2012). A general psychopathology model suggests that a single factor influences all symptoms across a range of known categorical and dimensional diagnoses, while specific psychopathology accounts for what is unique to a given set of symptoms above and beyond the general factor (Caspi et al, 2014;Lahey et al, 2012).…”
Section: General Psychopathology In Childhood and Adolescencementioning
confidence: 99%
“…The higher-order factor that accounts for the strong covariation of specific psychopathologies (e.g., internalizing, externalizing, and thought-disorder psychopathology) is referred to as general psychopathology or p factor (Caspi et al, 2014). Some have suggested that including a general psychopathology or p factor is necessary to fully conceptualize the structure of psychopathology (Avinun et al, 2021;Lahey et al, 2012). A general psychopathology model posits that a single factor influences all symptoms across a range of known categorical and dimensional diagnoses, while specific psychopathology accounts for what is unique to a given set of symptoms above and beyond the general factor (Caspi et al, 2014;Lahey et al, 2012).…”
Section: General Psychopathology In Childhood and Adolescencementioning
confidence: 99%